Transcriptional Memory-Like Imprints and Enhanced Functional Activity in γδ T Cells Following Resolution of Malaria Infection - Kumarasingha, Rasika; Ioannidis, Lisa J.; Abeysekera, Waruni; Studniberg, Stephanie; Wijesurendra, Dinidu; Mazhari, Ramin; Poole, Daniel P.; Mueller, Ivo; Schofield, Louis; Hansen, Diana S.; Eriksson, Emily M. (Frontiers in Immunology, 2020)
γδ T cells play an essential role in the immune response to many pathogens, including Plasmodium. However, long-lasting effects of infection on the γδ T cell population still remain inadequately understood. This study focused on assessing molecular and functional changes that persist in the γδ T cell population following resolution of malaria infection. We investigated transcriptional changes and memory-like functional capacity of malaria pre-exposed γδ T cells using a Plasmodium chabaudi infection model. We show that multiple genes associated with effector function (chemokines, cytokines and cytotoxicity) and antigen-presentation were upregulated in P. chabaudi-exposed γδ T cells compared to γδ T cells from naïve mice. This transcriptional profile was positively correlated with profiles observed in conventional memory CD8+ T cells and was accompanied by enhanced reactivation upon secondary encounter with Plasmodium-infected red blood cells in vitro. Collectively our data demonstrate that Plasmodium exposure result in “memory-like imprints” in the γδ T cell population and also promotes γδ T cells that can support antigen-presentation during subsequent infections.